THE RELATIONSHIP BETWEEN MANAGEMENT FUNCTION IMPLEMENTATION, SOCIAL CAPITAL AND BUSINESS PERFORMANCE OF SMALL CRAFT INDUSTRIES: THE MEDIATING EFFECT OF COMPETITIVE ADVANTAGE - Husni Hasbullah; Rohman Wilian; Al Parok; Dahmiri Dahmiri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
The research objective is to describe and model the relationship between the application of management functions, social capital and business performance of small craft industries with the mediating effect of competitive advantage in small craft industries in Jambi City. The research respondents are small craft industry businesses located in regencies/cities in Jambi City. The types of data used are primary and secondary data. Primary data was obtained by distributing questionnaires to small craft entrepreneurs and the results of interviews to key respondents using interview guides, while secondary data was obtained from various interest groups and literature. The classical test was performed with validity test, reliability test and normality test. Two approaches were used to analyze the data, namely qualitative and quantitative approaches using Structural Equation Modeling (SEM). From the results it is concluded that the management function has a significant positive impact on business activity, social capital has a significant positive impact on business activity, competitive advantage has a significant impact on business activity, management function has an impact on business activity through competitive. benefits, and social. Capital has a significant positive impact on business outcomes through competitive advantage